2018
DOI: 10.1111/ped.13492
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in the early phase of acute encephalopathy

Abstract: Age at onset, presence of BZD-resistant SE, and AST are associated with a poor prognosis in AE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…When cytolysis occurs or the cell membrane is destroyed, LDH is released into the blood, resulting in an increase in serum LDH ( 4 ). LDH activity can be detected in malignant tumor tissues and leukemic cells ( 5 ), and serum LDH levels are correlated with the prognosis of adult T-cell leukemia-lymphoma ( 6 ), prostate cancer ( 7 ), acute myeloid leukemia ( 8 ), melanoma ( 9 ), neuroblastoma ( 10 ), glioblastoma multiforme ( 11 ), acute encephalopathy ( 12 ), and Mycoplasma pneumoniae pneumonia ( 13 ). Serum LDH levels reflect the degree of brain tissue injury, and Yu et al demonstrated that serum LDH activity is associated with middle cerebral artery occlusion in a dose-dependent manner ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…When cytolysis occurs or the cell membrane is destroyed, LDH is released into the blood, resulting in an increase in serum LDH ( 4 ). LDH activity can be detected in malignant tumor tissues and leukemic cells ( 5 ), and serum LDH levels are correlated with the prognosis of adult T-cell leukemia-lymphoma ( 6 ), prostate cancer ( 7 ), acute myeloid leukemia ( 8 ), melanoma ( 9 ), neuroblastoma ( 10 ), glioblastoma multiforme ( 11 ), acute encephalopathy ( 12 ), and Mycoplasma pneumoniae pneumonia ( 13 ). Serum LDH levels reflect the degree of brain tissue injury, and Yu et al demonstrated that serum LDH activity is associated with middle cerebral artery occlusion in a dose-dependent manner ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] However, a previous study reported that the platelet count in acute encephalopathy is higher in the poor prognosis group than in the good prognosis group (median 39.5 × 10 4 /μL vs. 25.1 × 10 4 /μL). [ 18 ] In this study, there was only 1 case with a platelet count of <10 × 10 4 /μL in the steroid pulse group, and none in the no steroid pulse group. Therefore, the relationship between a low platelet count and prognosis remains unknown.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding the differences in the platelet count, a previous study indicated that levels of < 10 × 10 4 /µL were a poor prognostic factor in in uenza encephalopathy [19]. However, a previous study reported that the platelet count in acute encephalopathy is higher in the poor prognosis group than in the good prognosis group (median 39.5 × 10 4 /µL vs. 25.1 × 10 4 /µL) [18]. In this study, there was only one case with a platelet count of < 10 × 10 4 /µL in the steroid pulse group, and none in the no steroid pulse group.…”
Section: Discussionmentioning
confidence: 95%
“…Other reports on the relationship between acute encephalopathy and AST elevation indicate that AST ≥ 46 IU/L on admission is an independent prognostic factor (odds ratio 18.5) for poor outcome in acute encephalopathy [18], while AST elevation on admission in in uenza encephalopathy is a predictor of mortality (odds ratio for AST < 100: 100-500: >500 = 1: 5.45: 17.38) [18,19]. We found that 60% of participants had severe sequelae, which is consistent with previous reports and indicates that AST elevation predicts poor prognosis early in the disease.…”
Section: Discussionmentioning
confidence: 95%